The Effect of Grain Size on Radon Exhalation Rate in Soil Samples of Dera Ismail Khan in Pakistan - Tabassum Nasir; Nisar Ahmad (Journal of Basic & Applied Sciences, 2021)
Radon concentration and its exhalation rate has been measured from twenty five soil samples collected from seven different locations of Dera Ismail Khan, in the north west of Pakistan. These samples were crushed after drying and passed through sieves with different sizes of pores to get three grain sizes, £0.595 mm, 0.595-2.00 mm and 2.00-4.00 mm of soil. CR-39 based NRPB (National Radiological Protection Board) radon dosimeters have been used to measure the radon concentration and exhalation rates. The maximum average value of radon exhalation rate has found to be: (3.57±0.38) Bq m-2 hr-1 in the samples having grain size 2.00-4.00 mm and the minimum as: (2.21±0.26) Bq m-2hr-1, in the samples with grain size £ 0.0595 mm. This indicates that the radon exhalation rate increases with the grain size. The maximum average value of radon exhalation rate has been found in samples collected from river side where soil texture is silty clay loam. The obtained values of radon exhalation rate for all the samples are well below the world average value of 57.60 Bq m-2 hr-1.